On the Semiosphere, Revisited - Marinakis, Yorgos (Signs - International Journal of Semiotics, 2012)
The semiosphere is frequently described as a topos of complexification, namely discontinuous or heterogeneous, recursive or self-reflexive, stochastic, radically subjective, and capable of simultaneous multiple perspectives. While the topos of complexification describes the gross morphology of a model, it is not a model adequate for explaining phenomena or making predictions. The ecological theory of dual hierarchies is proposed as a framework for developing models of the semiosphere that are appropriately limited in scope and scale. In particular the semiosphere is modeled as a dual hierarchy of semiotic spaces, the dual hierarchies corresponding to the semiosis that is occurring within the dual hierarchies of ecological organization. This framework immediately solves several theoretical problems, such as clearing up conceptual inconsistencies in Lotman’s concept of semiosphere.